Desenvolvimento de sucos a base de vegetais com probióticos - ALVES, Denúsia Maria de Moraes (2023)
Juices involving fruits such as cajá and vegetables as joão-gomes can be promising products for the probiotics production. These species have high agronomic and socioeconomic potential and, as they are part of the local agrobidioversity, they can bring a strong boost to family farming. This study aimed to develop and characterize mixed probiotic juices from cajá (Spondias mombin) and teas from the leaves or stems of joão-gomes (Talinum triangulare). The research was divided into four stages. In the first stage, a consumer attitude survey was carried out. In the second stage, the ideal conditions for the growth of the probiotic Lacticaseibacillus casei in mixed juices based on cajá and joão-gomes leaves and stems were determined. In the third stage, the sensory evaluation was carried out in the developed juices. In the fourth step, the juice stability was evaluated. According to the results, for the consumer attitude survey, word association indicated that consumers associated the product mainly with healthiness and sensory characteristics, indicating that words related to these dimensions may be the main motivations for consuming these products. products. As for the ideal conditions for the beverages production, those containing cajá and joão-gomes leaves were 45.43% of mixed base and 6.1 of initial pH and that with cajá and stems were 40.45% of mixed base and 6. 0 initial pH. For both beverages, the ideal fermentation time was 14 hours. With regard to color, fermentation increased the lightness and yellowness of the juices. For the sensory evaluation, the highest acceptance (p<0.05) was for juices containing cajá and joão-gomes stems, regardless of the sweetening substance used (sugar or stevia). According to the Check-All-That Apply data, the juices of cajá and joão-gomes leaves with added sugar were related to the terms green color, dark color, cloudy and concentrated. On the other hand, the juices of cajá and joão gomes leaves added stevia to the terms aroma of leaves and bitter taste. The juices of cajá and joão-gomes stems with added sugar were related to the terms yellow color, cajá aroma and tasty. Finally, the juices of cajá and joão-gomes stems added with stevia were related to the terms salty and thin taste. During storage for 42 days, it was observed that in beverages with added sugar, there was an increase in viable cells counts, while in those with stevia, a reduction was observed. Regarding the pH, it was observed that there was a reduction of this parameter in the mixed probiotic juices during storage. With regard to phenolic compounds, a reduction was observed during storage in all juices. Juices containing cajá and joão-gomes leaves had higher values than those with cajá and stems. The antioxidant activity measured by the DPPH and ABTS methods also reduced with storage. In this way, the mixed drinks proved to be good matrices to carry the probiotic microorganism. In this study, the drinks with the most prominence were cajá juices and joão-gomes stems.